DAMPAK MEDIA SOSIAL TERHADAP KONFLIK DI MASYARAKAT - Hanifah Nur Erma; Dede Santika; Iffah Nurhasanah; Inda Lestari (Edusoshum : Journal of Islamic Education and Social Humanities, 2022)
Along with the development of technology, social media has become one of the products of the 4.0 revolution period, which has progressed rapidly. Through social media, everything can be reached in a short distance and time. However, there is an impact from this progress, one of which is the development of social conflict in society. The purpose of this research is to provide an analysis and study of the impact of social media on society. This research method is in the form of library research taken from texts that discuss social media. The results of the study show that social media can trigger conflicts in the community if users are not wise in filtering content on social media. The existence of social media also has a positive impact on society as an example of how information is received by the public more quickly in educational programs. The ease of life is also felt by the community with the existence of social media. So social media users need to be educated on the wise use of social media and take benefits in people's lives to overcome conflicts that exist in society.